Skeletal and Dental Development Preserve Evidence of Energetic Stress in the Moose of Isle Royale - Brown, Caitlin; Rinaldi, Caroline E.; Ripple, William J.; Van Valkenburgh, Blaire (Frontiers in Ecology and Evolution, 2020)
Food shortages can leave diagnostic, and in the case of the dentition, irreversible changes in mineralized tissue that persist into historical and fossil records. Consequently, developmental defects of tooth enamel might be used to track ungulate population irruptions or declines in resource availability but dental tissue’s capacity for preserving historical population density changes has yet to be investigated in wild populations. We test the ability of macroscopic enamel defects, mandible and metapodial lengths to track changes in the well-known insular moose population of Isle Royale National Park. Our study demonstrates that 1) a moose density threshold exists on the island above which there is a significant decrease in mandible and metatarsus length and a concomitant increase in enamel hypoplasias, 2) food limitation has a more pronounced effect on male than female skeletal and dental growth, and 3) combined data from tooth enamel hypoplasias and bone lengths reflect the relative density of this ungulate population, and should be broadly applicable to other ungulate osteological samples. Developmental defects in dental enamel were among the highest recorded in a wild population, and even during low-density intervals the population density of Isle Royale moose has been high enough to negatively impact skeletal and dental growth, indicating the comparatively poor health of this isolated century-old ecosystem.